Sustainable Nanocellulose UV Filters for Photovoltaic Applications: Comparison of Red Onion (Allium cepa) Extract, Iron Ions, and Colloidal Lignin - Nizamov, Rustem; Poskela, Aapo; Kaschuk, Joice; Henn, Karl Alexander; Grande, Rafael; Granroth, Sari; Nyberg, Mikael; Esmaeilzadeh, Maryam; Vapaavuori, Jaana; Österberg, Monika; Miettunen, Kati (American Chemical Society (ACS), 2025)
This study explores the stability of cellulose-based films as sustainable ultraviolet (UV) light filter films for optoelectronic applications. To address the gap in assessing the long-term performance of biobased UV filters in practical applications, these films were applied to dye-sensitized solar cells (DSSCs)─devices that are extremely prone to UV degradation. This research employs cellulose nanofiber (CNF) and 2,2,6,6-tetramethylpiperidine-1-oxyl radical (TEMPO)-oxidized CNF (TOCNF) based films as a basis for UV filter materials, providing the first insights into their extended reliability and functionality. The films include TOCNFs with physically and chemically physically cross-linked iron ions (III) forms (TOCNF-Fe3+ and TOCNF-ECH Fe3+), CNF film with lignin nanoparticles deposition (CNF-LNP), and CNF film dyed with red onion (Allium cepa) skin extract (CNF-ROE). UV–vis-NIR spectroscopy demonstrated that CNF-ROE blocked 99.9% of radiation below 400 nm, showcasing its superior UV-blocking capability compared to the other materials tested here. The biobased films caused a more significant loss in transmittance in the visible range than the commercial reference. Among them, CNF-ROE, which offered the highest UV protection, also demonstrated the highest light transmittance, exceeding 80% in the 650–1100 nm range. During 1000 h of light soaking testing, DSSCs covered with CNF-ROE presented minimal visual discoloration, or bleaching, of the electrolyte even compared to the cells protected by the commercial UV filter film used as a benchmark. Predictive modeling based on the accelerated aging test projected that CNF-ROE could protect DSSCs for approximately 8500 h, compared to only 1500 h with the commercial filter. To summarize, CNF-ROE stood out as a promising biobased UV filter alternative, particularly it maintained well its performance throughout prolonged exposure. The study highlights the effectiveness of biobased UV filter films for optoelectronic applications, particularly where sustainable and durable materials are paramount.